The Role of Chinese Migration and Investment in Europe - Chung, Mona (The journal of contemporary issues in business and government, 2016)
Although global Chinese migration is not a new phenomenon, its nexus with investment and specifically into Europe has had a significant impact on the economic landscape. This is largely a result of the rapid Chinese economic growth of the past thirty years. The impact of this phenomenon, though, is not only felt on an economic level; Chinese migration and investment into Europe have also been shown to have important political, cultural and societal aspects. For decades scholars have largely treated research into migration and investment as two parallel but separate phenomena with virtually no studies investigating the relationship between the two, in particular in relation to Europe. This is partially explained by the speed with which China became an economic powerhouse and the unique relationship between investment and migration. A further layer of complexity is added by China’s unique economy as state-owned enterprises (SOE) and their ability to globalise are quite distinct from the normal firm investment scenario. This article outlines and describes the characteristics of Chinese migration into Europe. By separating the discussion into Western and Eastern Europe, the article presents a theoretical explanation of China’s approach to European investment and explores the nexus between migration and investment. The article then goes on to identify the drivers, trends, and immigration policies in the relevant geographical areas as well as examining the four major methods used by Chinese migrants as the vehicle for entry into Europe. The article uncovers the special nature of SOEs, which distinguishes investment coming from Chinese public and private sources, concluding with a discussion on the importance of Chinese migration and investment into European firms as well as the implications and impacts of this strategy.